Reproductive Characteristics of the Stripetail Darter (Etheostoma kennicotti) Relative to Monogenean Gill Parasite Infection in Estill Fork in North Alabama - Joy L. Garcia; Corinne N. Peacher; Zeina Celine Sleiman; Bruce Stallsmith (Southeastern Fishes Council Proceedings, 2024)
What relationship exists between Aethycteron sp. gill parasite infection and the reproductive characteristics of stripetail darters, Etheostoma kennicotti? 450 E. kennicotti were collected over 11 months from Estill Fork in Jackson County, Alabama. Gonads were removed and photographed. All oocytes were counted and then classified into one of four developmental stages based on size and appearance. Gill parasites belonging to the monogenean genus Aethycteron were excised, photographed, and counted. Sexual dimorphism in length and mass was observed in E. kennicotti. The number of males found at the 25> mm SL range far outnumbered the females while almost all individuals 25< mm SL were females. A high gonadosomatic index (GSI) was found in the females, with large (2 mm) size clutch oocytes. Female E. kennicotti were observed to be reproductively mature starting at 19 mm SL. Prevalence and intensity of infection by Aethycteron sp. parasites were high in both males and females, with prevalence reaching 90% in breeding condition individuals. Two hypotheses were tested to explain these phenomena. The first is that the lack of females in the larger size categories may be the result of a high cost of reproduction resulting in near-term reproduction being paid for at the expense of long-term survival. The second hypothesis tested is that fecundity compensation in females potentially causes the early reproductive maturation. The gender imbalance is likely the result of the sheer costs involved with reproduction, indicating high investment in current reproductive success with limited longer-term survival consistent with the fecundity compensation hypothesis.
Keywords: Dactylogyrid; Aethycteron; Gill Parasites; Percidae